2020
DOI: 10.1017/cjn.2020.159
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Treatment of Functional Neurological Disorder: A Scoping Review

Abstract: Background: The aim of this scoping review is to describe the characteristics of patients requiring admission to hospital for functional neurological disorder (FND), assess interventions provided, and evaluate outcomes in the context of acute hospital presentation or elective admission with chronic symptoms (>3 months). Methods: A scoping review was performed. Included articles described adult patients admitted with FND to an inpatient care setting. Articles focusing on psychogenic no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 41 publications
(120 reference statements)
0
34
0
Order By: Relevance
“…(3) improved quality of services by monitoring patients in their home rather than traveling to distant treatment centers can also improve the cost-effectiveness of interventions [53]. The recent scoping review by Gilmour and Jenkins [28] reported that while rehabilitation was consistently used as an inpatient intervention with positive results, most patients returned to independent function at discharge despite persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) improved quality of services by monitoring patients in their home rather than traveling to distant treatment centers can also improve the cost-effectiveness of interventions [53]. The recent scoping review by Gilmour and Jenkins [28] reported that while rehabilitation was consistently used as an inpatient intervention with positive results, most patients returned to independent function at discharge despite persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuncts and innovations to improve access to specialist rehabilitation treatment by qualified professionals aided by advanced devices (i.e., tele/remote health and wearable technology) and long-term monitoring have seldom been explored in patients with FMDs [ 19 , 34 ]. By exploring a staged approach to FMDs, such as acute admission to specialized centers followed by outpatient programs ensuring appropriate treatment, the burden on the care system can be reduced [ 27 , 28 ]. Within this perspective, telemedicine offers many advantages: (1) regular communication between clinicians and real-time assessment of the patient’s environment; (2) patient improvement in satisfaction and quality of life, cutting the cost and labor of accessing health care; (3) improved quality of services by monitoring patients in their home rather than traveling to distant treatment centers can also improve the cost-effectiveness of interventions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor FND pathway was designed to have a fixed two-week endpoint. Other facilities have reported widely variable length of stays (LOS) for inpatient rehabilitation, ranging from a few days to several months (Demartini et al, 2014;Gilmour et. al, 2021;.…”
Section: Pathway Structurementioning
confidence: 99%
“…There is a growing body of evidence highlighting the benefits of FND treatment. In a scoping review of inpatient treatment of 458 patients with FND, 90% showed at least some improvement in symptoms at discharge (Gilmour & Jenkins, 2021 ). Additionally, positive outcomes have been reported in shorter outpatient-only models of rehabilitation therapies (Czarnecki et al, 2012 ).…”
Section: Clinical and Ethical Challengesmentioning
confidence: 99%